IMPLEMENTASI PROGRAM KAMPUNG KELUARGA BERENCANA (KAMPUNG KB) DI KABUPATEN NIAS UTARA - Telaumbanua, Exaudi; Rochadi, R.Kintoko; Ketaren, Otniel; Silitonga, Evawani Martalena; Sinaga, Janno; Sinaga, Taruli Rohana (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
The lack of optimal development in the KB Village that has been formed in North Nias Regency is caused by many factors, including the lack of the existing budget (government policy) in supporting the KB village program, lack of facilities and infrastructure (there is no secretariat for the KB village working group), Lack of awareness (participation) The community in carrying out the KB village program and the minimal role of family resilience in KB village activities. The type of research used in this study is a type of research with a qualitative approach. The planned informants include the P2AP2KB Office, PLKB, Village Heads, KB Village Working Group Management and some from the community. Understanding how to explore the implementation of the KB Village Program in North Nias Regency in 2020. This research was conducted in May 2020 and the research location was aimed at a place where the KB Village is not optimal in carrying out the Family Planning Village Program activities. Data collection techniques in this study are: Focus Group Discussion (FGD), Interview, Documentation, Observation. The results of the study are the absence of policies taken by the Regional Government of North Nias Regency in the KB Village activity program, the absence of the provision of facilities and infrastructure that can be provided from the village government, the low awareness of the community in carrying out the Kampung KB program activities, the influence of policies, participation, facilities and infrastructure and family resilience are very influential in the success of the Kampung KB program activities. The suggestion in this study is that it is hoped that the Regional Government of North Nias Regency can make a policy that can be useful in the activities of this KB Village Program so that the Village Government can boldly carry out tasks and functions in the KB Village Program. Keywords: KB Village Program Implementation The lack of optimal development in the KB Village that has been formed in North Nias Regency is caused by many factors, including the lack of the existing budget (government policy) in supporting the KB village program, lack of facilities and infrastructure (there is no secretariat for the KB village working group), Lack of awareness (participation) The community in carrying out the KB village program and the minimal role of family resilience in KB village activities. The type of research used in this study is a type of research with a qualitative approach. The planned informants include the P2AP2KB Office, PLKB, Village Heads, KB Village Working Group Management and some from the community. Understanding how to explore the implementation of the KB Village Program in North Nias Regency in 2020. This research was conducted in May 2020 and the research location was aimed at a place where the KB Village is not optimal in carrying out the Family Planning Village Program activities. Data collection techniques in this study are: Focus Group Discussion (FGD), Interview, Documentation, Observation. The results of the study are the absence of policies taken by the Regional Government of North Nias Regency in the KB Village activity program, the absence of the provision of facilities and infrastructure that can be provided from the village government, the low awareness of the community in carrying out the Kampung KB program activities, the influence of policies, participation, facilities and infrastructure and family resilience are very influential in the success of the Kampung KB program activities. The suggestion in this study is that it is hoped that the Regional Government of North Nias Regency can make a policy that can be useful in the activities of this KB Village Program so that the Village Government can boldly carry out tasks and functions in the KB Village Program. Keywords: KB Village Program Implementation